2019
DOI: 10.1002/joom.1019
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and empirical evidence of behavioral and production line factors that influence helping behavior

Abstract: A poorly motivated workforce can have a negative impact on the productivity of production lines and firm performance. One factor that can counter the effects of poorly performing workers is if stronger colleagues step in and assist them. Leveraging theory from the organizational citizenship behavior literature, this study examines how behavioral and production line factors influence individuals to help team members in a production line experiment. Study findings are that perceptions of social loafing and mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 92 publications
1
28
0
1
Order By: Relevance
“…There are also good examples of mixed‐method approaches. Cantor and Jin (2019) examined how production line factors influence intrinsically motivated helping behaviors, and do not incorporate use of incentives in their main study. The absence of incentives in this instance represents an appropriate match of research question, context, and design choice.…”
Section: Considerations Of Different Research Design Choices That Maxmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also good examples of mixed‐method approaches. Cantor and Jin (2019) examined how production line factors influence intrinsically motivated helping behaviors, and do not incorporate use of incentives in their main study. The absence of incentives in this instance represents an appropriate match of research question, context, and design choice.…”
Section: Considerations Of Different Research Design Choices That Maxmentioning
confidence: 99%
“…The absence of incentives in this instance represents an appropriate match of research question, context, and design choice. In post hoc tests, Cantor and Jin (2019) introduced team‐ and individual‐level performance incentives, and found that while individual incentives were not related to helping, team‐based incentives were. Again, the research question (i.e., do incentives influence helping?)…”
Section: Considerations Of Different Research Design Choices That Maxmentioning
confidence: 99%
“…The investigation of a trade-off between tooling costs and throughput improvement remains as future work. Moreover, the impact of the social loafing effect as investigated by Cantor and Jin [30] also needs to be examined. Our model is limited to only a two-stage tandem dedicated production line.…”
Section: Resultsmentioning
confidence: 99%
“…An insufficient motivation of the workforce may cause a negative impact on the productivity of production lines and business performance. The study [18] examines influence of behavioural and production line factors on subjects working in teams.…”
Section: Introductionmentioning
confidence: 99%